C. B. Pierce, Charter and Ordinances of the City of Leavenworth 45 (1863) - (:unkn) unknown (My University, 1863)
An Ordinance Relating to Misdemeanors, § 23: Prohibited the carrying of any concealed "pistol, dirk, bowie knife, revolver, slung shot, billy, brass, lead or iron knuckles, or any other deadly weapon within this city." Punishable by a fine of $3-100.
Keywords: CARRY - CONCEALED